Determinan Minat Membayar Zakat Generasi Milenial Jawa Barat Melalui Platform Fintech - Mais, Rimi Gusliana; Munir, Munir; Setiawan, Desy Amaliati; Aldina, Nabiilah (Ma'soem University, 2025)
This study aims to determine and analyze the factors that influence the interest of the millennial generation in paying zakat online through the fintech platform. The sample used in this study was 108 respondents from the millennial generation who live or are domiciled in the West Java region. There are three independent variables used in this study, namely Income, Religiosity, and Accountability. While the dependent variable used is the interest of the millennial generation in paying zakat online. The sample selection method in this study uses a purposive sampling technique. This study uses a descriptive research method with a type of research using a quantitative approach, which is measured by the panel data regression method using the Statistical Product and Service Solution (SPSS) version 23. The results of this study indicate that income and accountability have a significant positive effect on the interest of the West Java millennial generation in paying zakat online through the fintech platform, while religiosity does not affect the interest of the West Java millennial generation in paying zakat online through the fintech platform.